2020
DOI: 10.3892/etm.2020.9042
|View full text |Cite
|
Sign up to set email alerts
|

Expression of serum miR‑27b and miR‑451 in patients with congenital heart disease associated pulmonary artery hypertension and risk factor analysis

Abstract: This study investigated expression of serum miR-27b and miR-451 in patients with congenital heart disease associated pulmonary arterial hypertension (CHD-PAH), and analyzed the risk factors of CHD-PAH. A total of 114 patients with CHD admitted to the First Affiliated Hospital of the University of South China were recruited and allocated into a study group (61 patients with PAH) and a control group (53 patients without PAH). Reverse transcription-polymerase chain reaction (RT-PCR) was employed for the qualifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…In a rat model of burn-induced acute lung damage, miR-451 expression is increased in lung endothelial cells, which promotes the increase of permeability of lung endothelial cells and inhibits the angiogenesis of lung endothelial cells, showing potential of burn treating [ 25 ]. Long et al found that decreased expression of miR-451 in serum of CHD-PAH patients, which is associated with BNP, ADMA, and disease severity [ 14 ]. Muscularization of hitherto nonmuscular arteries and remodeling of the pulmonary vasculature are two of PAH's primary hallmarks [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a rat model of burn-induced acute lung damage, miR-451 expression is increased in lung endothelial cells, which promotes the increase of permeability of lung endothelial cells and inhibits the angiogenesis of lung endothelial cells, showing potential of burn treating [ 25 ]. Long et al found that decreased expression of miR-451 in serum of CHD-PAH patients, which is associated with BNP, ADMA, and disease severity [ 14 ]. Muscularization of hitherto nonmuscular arteries and remodeling of the pulmonary vasculature are two of PAH's primary hallmarks [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-451 is mainly expressed in cardiac myocytes and is upregulated in PHA patients and hypoxia-induced PAH rat models, and changes in its serum content affect the function of pulmonary artery smooth muscle cells [ 13 ]. Long et al found that the miR-451 expression was decreased in serum of patients with CHD-PAH [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, circulating miRNAs are a useful diagnostic and prognostic biomarker of PAH [ 49 , 50 ]. Previous studies have reported the association of circulating miRNAs, including miR-27b and miR-451 [ 51 ], miR-125a-5p [ 52 ], miR-509-3p [ 53 ], miR-206 [ 54 ], miR-483 [ 55 ], miR-211 [ 56 ], miR-143 [ 57 ], miR-596 [ 58 ], and miR-208-Mef2 [ 59 ] axis with the prognosis of PAH. The miR-29 family members have been reported as anti-fibrotic miRNAs [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“… 31 In congenital heart disease associated pulmonary artery hypertension, elevated serum miR-27b is considered to be of great significance in the diagnosis and evaluation of congenital heart disease associated pulmonary artery hypertension. 32 Due to the significant difference in expression of miR-27b between normal individuals and ACAS patients, its diagnostic value for ACAS was evaluated. A ROC curve based on serum miR-27b was constructed.…”
Section: Discussionmentioning
confidence: 99%